2012
DOI: 10.1007/s00267-012-9847-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quarries Rehabilitation Scenarios: A Case Study Within the Metropolitan Area of Bari (Italy)

Abstract: This paper addresses quarries rehabilitation issue within a Metropolitan Area. Areas where mining activity is carried out have been subjected to physical and environmental degradation linked both to pursue the building materials extraction and to the city expansion continuously asking for new areas to be developed with residential and service functions. These changes also occurred where environmental and landscape values are present. It has been therefore pointed out the issue of such areas redevelopment that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Quarry re-greening and rehabilitation focus on reducing the impact of quarrying, enhancement of sustainable development and increasing economic gains from the abandoned quarries (Dongdong et al, 2009;Mendes et al, 2014). There are many environmental repair approaches geared towards quarried land to enhance its economic value (Dal Sasso et al, 2012). The different quarry sites have different degree of disturbance, thus priorities in rehabilitation should focus on the hierarchy of impacts (Mhlongo and Amponsah-Dacosta, 2015;Mavrommatis and Menegaki, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Quarry re-greening and rehabilitation focus on reducing the impact of quarrying, enhancement of sustainable development and increasing economic gains from the abandoned quarries (Dongdong et al, 2009;Mendes et al, 2014). There are many environmental repair approaches geared towards quarried land to enhance its economic value (Dal Sasso et al, 2012). The different quarry sites have different degree of disturbance, thus priorities in rehabilitation should focus on the hierarchy of impacts (Mhlongo and Amponsah-Dacosta, 2015;Mavrommatis and Menegaki, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, minimize the harmful effects from rock processing that cause pollution to surface and groundwater resources. Dal Sasso et al (2012) identified quarry reuse alternatives with the application of a twostep methodology, comprising a multi-criteria analysis related to a site-specific level and territorial indicators checking over the wide area.…”
Section: Introductionmentioning
confidence: 99%
“…5. The environmental impact of increasing, widespread excavations surrounding urban areas has been described for this and other regions (Pereyra and Rimoldi, 2003;Pereyra, 2004;Subba Rao and Prathap Reddy, 2004;Rivas et al, 2006;Jordan, 2009;Zuquette et al, 2009;Dal Sasso et al, 2012;Hurtado, 2015). The impact on the humid Pampa includes:…”
Section: The Brick Industry In the Humid Pampa And Its Environmental mentioning
confidence: 92%